A Retrospective Evaluation on One to Six Years ITI Dental Implants Application Based on Clinical and Radiographic Parameters - AR Rokn; S.A Miremadi; A Nikbakht (Tehran University of Medical Sciences, 2003)
In the past two decades, replacement of the missing teeth with implant borne prosthesis has become a treatment modality, accepted by the scientific community for fully and partially edentulous patients. The aim of the present study is to evaluate retrospectively, 502 ITI dental implants application, in partial and complete edentulous patients, treated in two private centers, based on clinical and radiographic parameters.One hundred and forty patients, with 502 ITI dental implants, who were treated from 1994 to 2000 in two private centers, were investigated. For such patientsT a minimum of one year and a maximum of six years were passed since prosthesis placement over implants, so they were cooperative subjects. There was a significant relation between implant type and bone loss, so was between the presence and absence of BOP and the rate of bone loss. From totality 502 implants, 6 implants (28%) and 4 implants (1.4%) were lost, in maxilla and mandible, respectively. The total success rate was 98%. This rate, in maxilla with 212 implants was 97.2% and in mandible with 90 implants was 98.6%. The mean value of bone loss (RBL) and periodontal pocket depth (PPD) during 6 years, for the remaning 492 implants were 0.93±0.39mm and 1.99mm, respectively. The results showed that ITI dental implants, with a success rate of more than 97%, can be used as a desirable treatment choice in partial and complete edentulous patients.